2012
DOI: 10.1017/s1473550412000055
|View full text |Cite
|
Sign up to set email alerts
|

The galactic habitable zone in elliptical galaxies

Abstract: The concept of a Galactic Habitable Zone (GHZ) was introduced for the Milky Way galaxy a decade ago as an extension of the earlier concept of the Circumstellar Habitable Zone. In this work, we consider the extension of the concept of a GHZ to other types of galaxies by considering two elliptical galaxies as examples, M87 and M32. We argue that the defining feature of the GHZ is the probability of planet formation which has been assumed to depend on the metallicity. We have compared the metallicity distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Huang 1959;Hart 1979;Kasting et al 1993;Rushby et al 2013;Kopparapu et al 2013;Güedel et al 2014). A few theoretical works have extended SHZ calculations to estimate habitable zones at galactic scales, the Galactic Habitable Zone (GHZ; Gonzalez et al 2001) for specific galaxies like the Milky Way (MW) and nearby ellipticals (Suthar & McKay 2012;Carigi & Meneses-Goytia 2013). Approaches to modelling the GHZ of the MW range from using metallicity and star formation distributions (Gonzalez et al 2001) to sophisticated descriptions of the distribution of terrestrial planets (Lineweaver et al 2004) to modelling individual star systems (Gowanlock et al 2011) to tracing the co-evolution of the GHZ and the assembly of the MW (and Andromeda) using cosmological simulations (Forgan et al 2015, submitted to International Journal of Astrobiology).…”
Section: Introductionmentioning
confidence: 99%
“…Huang 1959;Hart 1979;Kasting et al 1993;Rushby et al 2013;Kopparapu et al 2013;Güedel et al 2014). A few theoretical works have extended SHZ calculations to estimate habitable zones at galactic scales, the Galactic Habitable Zone (GHZ; Gonzalez et al 2001) for specific galaxies like the Milky Way (MW) and nearby ellipticals (Suthar & McKay 2012;Carigi & Meneses-Goytia 2013). Approaches to modelling the GHZ of the MW range from using metallicity and star formation distributions (Gonzalez et al 2001) to sophisticated descriptions of the distribution of terrestrial planets (Lineweaver et al 2004) to modelling individual star systems (Gowanlock et al 2011) to tracing the co-evolution of the GHZ and the assembly of the MW (and Andromeda) using cosmological simulations (Forgan et al 2015, submitted to International Journal of Astrobiology).…”
Section: Introductionmentioning
confidence: 99%
“…Both these effects frame a wider question to what extent galactic environments significantly diverging from the one in which Solar System has formed and evolved are conducive to life. Hence, these studies have indirectly supported the conclusion of Suthar and McKay (2012) that early-type systems could be habitable as well, in sharp contrast to the rare-Earth dogma.…”
Section: Introduction: Cosmology and Habitabilitymentioning
confidence: 56%
“…Before that, it is important to notice that the interest in habitability of external galaxies has been reawakened recently by several interrelated developments which undermined the rare-Earth paradigm. For instance, the work of Suthar and McKay (2012) indicated that the low-metallicity wing of the extrasolar planet metallicity distribution is perfectly in accordance with the possibility that such planets exist in elliptical galaxies such as M87 and M32.…”
Section: Introduction: Cosmology and Habitabilitymentioning
confidence: 72%
“…They employed a GCE model to follow the evolution of the metallicity and the supernova rate in its disk and halo; they excluded the bulge given its high stellar density. Suthar and McKay [ 69 ] explored the GHZ for two elliptical galaxies, M32 and M87, but they only considered the effects of metallicity.…”
Section: The Chz Ghz and Cha Concepts And Habitable Planet Formatmentioning
confidence: 99%